Development of Google System (GS) Based Learning Management at a Leading Islamic Junior High School (Research at Ar-Rafi Drajat Junior High School, Bandung City) - Hendri Juhana; Badrudin Badrudin; Mohamad Erihadiana; Wasehudin Wasehudin (Lafadz Jaya Publisher, 2025)
This research was conducted based on the author's curiosity to understand more deeply how the implementation of Google System (GS) can support effective learning management at a Leading Islamic Junior High School, especially in the digital era. The author is interested in exploring how GS technology can facilitate an innovative, interactive, and relevant learning process to today's educational needs, especially in the context of strengthening Islamic values. In addition, this study aims to answer the challenges in integrating digital technology with an active learning approach that focuses on developing 21st century skills, such as critical thinking, creativity, and collaboration. This study aims to develop an effective GS-based learning management model to be implemented at a Leading Islamic Junior High School, focusing on a case study at Ar-Rafi Drajat Junior High School, Bandung City. This study uses a qualitative approach with a case study method, which involves data collection through in-depth interviews, participant observation, and document analysis. The focus of this study is to explore the application of GS in supporting innovative, relevant, and effective learning processes in the digital era. This study found the GS-Based Islamic-Integrative Learning Management Model. It is called the GS-Based Islamic-Integrative Learning Management Model because learning integrates general science and Islamic science supported by GS (Google System) technology. This GS-Based Islamic-Integrative Learning Management Model is a model with an Integrative Approach that focuses not only on intellectual intelligence but also spiritual intelligence. A Learning Management Model that seeks to combine intellectual, social-emotional, and spiritual dimensions to achieve integrative education with the help of GS technology.